2019
DOI: 10.1016/j.diagmicrobio.2019.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Mortality caused by extended-spectrum beta-lactamase–producing Enterobacteriaceae bacteremia; a case control study: alert to Enterobacteriaceae strains with high minimum inhibitory concentrations of piperacillin/tazobactam

Abstract: Purpose. The incidence of infections caused by extended-spectrum beta-lactamase-producing Enterobacteriaceae (ESBL-PE) has been recently increasing worldwide. ESBL-PE bacteremia has been associated with high mortality and has thus become a clinically critical issue. Accordingly, ESBL-PE strains with low susceptibility to piperacillin/tazobactam (PTZ) are a concern in clinical practice. This study aimed to assess the prognostic factors of patients with bacteremia due to ESBL-PE as well as the antimicrobial susc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…In all the studies, the time of death records was not similar. The majority of studies used 30-day mortality to evaluate the clinical outcomes of BSIs caused by ESBL-PE in patients with malignancy, [ 13 29 ] only one study did not report a particular time of death [ 30 ]. In studies that only enrolled oncological patients with ESBL-PE infections, the mortality of BSIs varied from 10.7 to 31.0%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all the studies, the time of death records was not similar. The majority of studies used 30-day mortality to evaluate the clinical outcomes of BSIs caused by ESBL-PE in patients with malignancy, [ 13 29 ] only one study did not report a particular time of death [ 30 ]. In studies that only enrolled oncological patients with ESBL-PE infections, the mortality of BSIs varied from 10.7 to 31.0%.…”
Section: Resultsmentioning
confidence: 99%
“…This can be explained by the fact that only three studies included patients with FN. Besides, some studies only enrolled a subset of FN patients, but the data were not accessible to analyze [ 13 , 14 , 16 , 21 , 24 , 25 , 30 , 34 , 40 ]. Among these studies, Kang CI et al reported that FN/ neutropenia was not the risk factor for mortality in BSIs caused by ESBL-PE among patients with malignancy [ 14 , 16 , 21 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…(38,39) Interestingly, FN was not associated with higher mortality in oncological patients with BSIs caused by ESBL-PE, which could be attributed to there are only three studies included patients with FN, while some studies enrolled a subset of FN patients, but the data were not accessible to analysis. (13,14,16,21,24,25,30,34,40) Among these studies, Kang CI et al…”
Section: Discussionmentioning
confidence: 99%
“…Besides, some studies only enrolled a subset of FN patients, but the data were not accessible to analyze. (13,14,16,21,24,25,30,34,40) Among these studies, Kang CI et al reported that FN/ neutropenia was not the risk factor for mortality in BSIs caused by ESBL-PE among patients with malignancy. (14,16,21,24) Hence, the accuracy of the conclusion needs to be further con rmed.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies used 30-day mortality to evaluate the clinical outcomes of BSIs caused by ESBL-PE in patients with malignancy, (13-29) only one study did not report a particular time of death. (30) In studies that only enrolled oncological patients with ESBL-PE infections, the mortality of BSIs varied from 10.7% to 31.0%. However, the mortality of BSIs varied from 4.8% to 51.0 % in studies that both enrolled ESBL-PE and non-ESBL-PE infections oncological patients, respectively.…”
Section: Mortalitymentioning
confidence: 99%